Evaluation of the Potential for Riverbank Filtration in Colombia (2015)
A first approach to the potential of riverbank filtration (RBF) to be used in Colombia as an alternative in the treatment of drinking water was the main focus of this dissertation. This technology involves removing water from a surface current through a well on the floodplain and use the aquifer as a physical, chemical and biological filter. RBF has been used in Europe for over a century, but its systematic study is relatively recent and so far, besides the United States, few countries have used, or even explored, its potential. In view of the high costs associated with conventional surface water treatment techniques used in the country, plus the fact that more than half the population has no access to water of good quality, and that apparently there are appropriate settings for the implementation of technical but there is no documentation about its use, it was decided to approach the problem from three different points of view that would enable an overall assessment to the real possibilities of applying RBF in the country in a successful manner. Stream-reach geomorphology was used in order to compare sites where RBF is currently operating to determine the existence of common features that could be employed to evaluate the potential of a new site with scarce information. In addition, an attempt was made to establish whether the high load of suspended sediments of Colombian rivers could be a limitation to the use of the technique. Secondly, two sites were chosen in Antioquia with wells located in floodplains and where the existence of a direct connection between aquifers and currents had been established. There, water sampling campaigns were carried out for quality analysis in the light of the current regulations to establish the degree of removal of certain compounds in the river water compared with the well water. In addition, the percentage of river-borne water in the well was determined using a chemical tracer. Finally, the potential of RBF in the removal of some pesticides currently used in Colombia was evaluated through column experiments and numerical modeling of contaminant transport. Overall positive results were obtained, suggesting that the implementation and use of RBF in the country are possible, and therefore the technique is considered a promising alternative in the treatment of drinking water. It is necessary, however, to do more research in order to understand more precisely some of the mechanisms behind the technique and the possible limitations associated with specific characteristics of the country and the local rivers, especially what has to do with climatic events, suspended sediment load and current dynamics.